2011
DOI: 10.1016/j.ajhg.2011.08.008
|View full text |Cite
|
Sign up to set email alerts
|

ST3GAL3 Mutations Impair the Development of Higher Cognitive Functions

Abstract: The genetic variants leading to impairment of intellectual performance are highly diverse and are still poorly understood. ST3GAL3 encodes the Golgi enzyme β-galactoside-α2,3-sialyltransferase-III that in humans predominantly forms the sialyl Lewis a epitope on proteins. ST3GAL3 resides on chromosome 1 within the MRT4 locus previously identified to associate with nonsyndromic autosomal recessive intellectual disability. We searched for the disease-causing mutations in the MRT4 family and a second independent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
111
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 49 publications
9
111
0
Order By: Relevance
“…[10][11][12][13] The introduction of next generation sequencing techniques dramatically changed this scenario, leading to the discovery of a rapidly increasing number of AR-NSID causative genes. In addition to mutations in TECR (MIM 610057), 14 MAN1B1 (MIM 604346), 15 and ST3GAL3 (MIM 606494), 16 32 putative novel genes causative of AR-NSID have been recently reported by Najmabadi et al 17 Of note, the latter studies used an exome sequencing approach targeted to chromosome regions identified by means of linkage analysis, limiting the search of causative genes to families with high imbreeding coefficient, rarely found in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The introduction of next generation sequencing techniques dramatically changed this scenario, leading to the discovery of a rapidly increasing number of AR-NSID causative genes. In addition to mutations in TECR (MIM 610057), 14 MAN1B1 (MIM 604346), 15 and ST3GAL3 (MIM 606494), 16 32 putative novel genes causative of AR-NSID have been recently reported by Najmabadi et al 17 Of note, the latter studies used an exome sequencing approach targeted to chromosome regions identified by means of linkage analysis, limiting the search of causative genes to families with high imbreeding coefficient, rarely found in western countries.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of sialyltransferase genes in mice often results in immune and hematologic phenotypes [47][48][49]. Very recently, mutations in the 2-3 sialyltransferase gene ST3GAL3 (OMIM ID: 606494) have been associated with nonsyndromic mental retardation [50]. The exact impact of ST3GAL3 deficiency on brain glycoproteins remains to be established.…”
Section: 2-3 Sia-transferase IIImentioning
confidence: 99%
“…In affected members of this family, which was ascertained and mapped previously by Najmabadi et al [45] on locus 1p34.1, Hu et al [1] identified two missense homozygous mutations in ST3GAL3 at positions either in exon 2 (c. 38C>A, p.Ala13Asp) or in exon 14 (c.1108G>T, p.Asp370Tyr), which resulted in a loss of activity in the transmembrane and catalytic domains, respectively. The identified genetic alterations in the N-terminal transmembrane domain and C-terminal catalytic domain of sialyltransferase prevented the formation of sialo-glyco conjugates due to mislocalization in cellular compartments other than the golgi apparatus, thereby causing ID in affected members [1,57] …”
Section: St3gal3mentioning
confidence: 99%
“…The ST3GAL3 (ST3 Beta-galactoside Alpha-2, 3-Sialyltransferase 3) gene (OMIM # 606494) was identified by Hu et al [1] as a NS-ARID causing gene in a large consanguineous Iranian family. The ST3GAL3 gene (NCBI RefSeqGene: NG_028196.1) consists of total 25 exons and spans a 223 kb region on chromosome 1p34.1.…”
Section: St3gal3mentioning
confidence: 99%
See 1 more Smart Citation